Numerical obtaining of the thermal profile during the passage of the heat source in the materials AISI 410, 304L and 430 (Research, Society and Development, 2020)
The finite element method is a numerical analysis capable of answering several transient, non-linear engineering problems. The objective of this work was to carry out an experimental research of numerical analysis via finite elements, in search of the answer to a thermal input in three stainless materials, namely AISI 410, AISI 304L and AISI 430. For this, the software Ansys® Academic 2020 was used. R1, plates were modeled in the dimensions of 150x200x2 mm, with a passage path for the heat source of 180 mm. The materials were created with their transient physical properties. The heat source adopted was Gaussian, taken from a mathematical extension for the software. Heat losses due to conduction in the part, convection and radiation in the environment were considered. The construction of the temperature profile of each material was built according to the maximum temperature reached, temperature at specific points and maximum temperature flow. The data of the material temperature profiles were compared using ANOVA statistical analysis, using the Tukey test. The results showed the possibility of carrying out simulation of welding processes with the adopted boundary conditions, showed that there is no difference in maximum temperature between the three materials, however there is a significant difference between the maximum temperature flows obtained between the three materials, fact justified by their differences in physical properties. In addition, the thermal profile data allows structural analysis of the materials, as well as predictions of paths to follow in adjusting experimental parameters.